Terahertz spectroscopy of human skin tissue models with different melanin content - Peralta, Xomalin G. (Biomed Opt Express, 2019)
Terahertz imaging has been proposed for burns and skin cancer identification. However, the role of melanocytes, melanosomes, melanin content and distribution in determining the terahertz optical properties of human skin has not been investigated. We use terahertz time domain spectroscopy to measure the optical properties of in vitro pigmented human skin tissue models from Asian, Black, and Caucasian donors. Spectra were collected at various time intervals and used to extract the absorption coefficient and index of refraction at terahertz frequencies. Our results indicate that the degree of cell differentiation and type of donor both contribute to the measured terahertz optical properties.